Fracture resistance of endodontically treated root obturated with AH plus, MTA Fillapex, OneFill and Neosealer (A comparative in vitro study) (Mustansiria Dental Journal, 2024)
Aim: The aim of this study is to evaluate and compare the fracture resistance of endodontically treated root obturated with four different root canal sealers.. Methods: Sixty extracted palatal root of upper molars were collected and sectioned to get a 11mm root length. All root canals were instrumented using edge endo X7 system rotary files and 35# size was the final size used to finish all the canals. After instrumentation the samples were divided into four groups of 15 samples in each according to the type of sealer used, a single cone obturation technique was used: Group 1: obturated with AH Plus sealer and gutta-percha. Group 2: obturated with Neosealer BC sealer and gutta-percha. Group 3: Obturated with MTA-Fillapex sealer and gutta-percha. Group 4: Obturated with OneFill BC sealer and gutta-percha. After incubation period of 7 days at 37°C and 100% humidity the samples covered with thin layer polyvinylsiloxane impression material to simulate a periodontal membrane and then molded in acrylic blocks so as to set the samples ready for fracture resistance test using universal testing machine at a cross head speed of 0.5mm/min., One-way ANOVA and Posthoc tests assessed the data statistically. Results: The results showed that fracture resistance was significantly higher in those canals that were filled with Neosealer BC sealer (69.90N) in comparison to the other different sealers used in the study (p≤0.05). Conclusion: Under the condition of this study, the following conclusions can be derived:• The application of any root canal sealers resulted in an enhancement of the resistance to fractures in teeth that have undergone endodontic treatment.• Neosealer Bioceramic sealer group showed the highest fracture resistance than other groups. Followed by Onefill bioceramic, MTA Fillapex and Ah plus.